Activation of Coconut Shell - Randu Wood Biochar and Its Use as Heterogeneous Catalyst Support for Biodiesel Production. (June 2019) - Pradana, Y S; Rochim, N; Mukaffa, H S; Satriawan, H B; Hidayat, A; Budiman, A
Abstract: In the last decade, biodiesel has been considered as one of attractive biofuels in function of replacing fossil-based diesel fuel and concerning on reduction of greenhouse gas release. For biodiesel production, the use of heterogeneous catalyst is a challenge to minimize problems related to the use of homogeneous catalyst. One of potential heterogeneous catalyst is activated carbon-based catalyst. This study investigated the effect of activating agents (hydrochloric acid and sulfuric acid), its concentration (0.5, 1.0, 1.5 and 2.0 N) and activation time (1.5, 3.0, 4.5 and 6.0 h) on iodine number of activated biochar (from coconut shell and Randu wood). The results showed that the highest iodine number (749.14 mg/g) was obtained from coconut shell biochar activated by sulfuric acid at concentration of 2 N and activation time of 6 h. Moreover, BET analysis of the best activated biochar resulted 30.88 m 2 /gcat of surface area, 3.26 x 10 −2 cm 3 /g of total pore volume and 2.11 nm of average pore radius. The performance test of this potassium-impregnated activated biochar in batch transesterification reaction (palm oil-methanol) presented 29.44 % of biodiesel conversion.